DOES LEARNING ENVIRONMENT MODERATES THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON ACCOUNTING STUDENTS’ CRITICAL THINKING DISPOSITION? - Amalia, Nova Tri Amalia; Fauzan, Slamet (Universitas Muhammadiyah Surakarta, 2024)
This research explored how emotional intelligence impacts critical thinking disposition, considering the learning environment as a potential moderating factor. Employing a quantitative explanatory survey approach, the research engaged a accidental selected sample of 164 students from accounting education programs. Data collection was facilitated through Google Forms and analyzed using Moderated Regression Analysis (MRA). The analysis revealed that emotional intelligence positively influences critical thinking disposition. Furthermore, it was found that the learning environment enhances the effect of emotional intelligence on critical thinking disposition. Therefore, enhancing students' emotional intelligence and cultivating a conducive learning environment can significantly bolster their critical thinking disposition.